Does intraoperative neuromonitoring during thyroidectomy reduce the risk of hypoparathyroidism? - Zehra Zeynep Keklikkiran; Ezgi Tatlisu; Muzaffer Akinci; Gamze Citlak (Journal of the Pakistan Medical Association)
Objectives: To evaluate the effect of intraoperative neuromonitoring on postoperative hypoparathyroidism after bilateral total thyroidectomy.